Doenças fúngicas da cultura da pitaia - Moura, Nevenka de Matos (2020)
The cultivation of pitaya can be an interesting source of income and diversification of the agricultural activity. It is considered a promising activity, as it is relatively simple to grow, produces beautiful fruits, which are rich in functional compounds, bringing benefits to those who consume it. Fungi can affect the fruits and the vegetative part of pitaya, compromising production and reducing the commercial value. Aiming to contribute with information about fungal diseases that affect the crop, the objetives of this study were (i.) to identify the fungi associated with the disease symptoms in both fruits and cladodes, through the evaluation of morphological markers and analysis of molecular phylogeny; (ii.) to evaluate the pathogenicity of fungi in fruits and cladodes; (iii.) to describe and illustrate the symptoms which the various fungi cause, and to support the diagnosis in the field and in the phytopathological clinic. A total of 24 isolates were obtained from southern Minas Gerais, Santa Catarina and the Federal District, which were identified by morphological markers as belonging to the genera Bipolaris (n = 4), Alternaria (n = 6), Colletotrichum (n = 4) and Fusarium (n = 10). Representative isolates of each genus were identified by molecular phylogeny at the species level and used in pathogenicity tests on fruits and cladodes by injection of a conidial suspension. All isolates tested induced disease symptoms, with differences according to the inoculated species. Fruits and cladodes showed black rot when inoculated with Bipolaris cactivora, longitudinal black spots on fruits and dry rot on cladodes (Alternaria alternata), aqueous rot with orange sporulation on fruits and internal tissue colonization in cladodes (Colletrotrichum siamense), and watery brown rot in cladodes and fruits (Fusarium proliferatum and F. sterilihyphosum). Fusarium oxysporum did not cause disease when inoculated in cladodes, but in fruits it induced symptoms of dry rot. To complete Koch's postulates, pathogens were re-isolated. The results generated contribute to the correct identification of pathogens and support an effective management of diseases, aiming to guarantee the sustainability of the culture and its economic viability.